Innovative Activity in Subjects of Entrepreneurship Based on Foreign Experience (Eurasian Journal of History, Geography and Economics, 2022)
The article describes the mechanism of implementation of innovative processes inbusiness entities and foreign experiences, and gives a brief description of the main toolsused in it. In the conclusion, proposals were developed on the feasibility of their use inlocal practice.